Numerical and Experimental Investigation of the Effect of Cavitation on Dual Clearance Squeeze Film Damper - Zhaojun Feng; Guihuo Luo; Hai Yang; Wangqun Deng; Wei Chen; Cheng Shen (Shock and Vibration)
A new dynamic model is developed for the dual clearance squeeze film damper (DCSFD) considering the effect of cavitation in this paper. The relationship between the eccentricities of the inner and outer films is achieved based on the equations of motion. The Reynolds equation and Rayleigh–Plesset equation are employed to describe the kinetic properties of DCSFD and the cavitation effect of film, respectively. Under the assumption of compressible fluid, the pressure distribution of DCSFD is finally obtained by the numerically iterative method. The film pressure distribution in the outer layer (including the positive and negative pressure zones) obtained from the experimental test agrees well with the numerical prediction, which verifies the validity of the proposed numerical model. In Section 5, the effects of oil temperature, inlet pressure, eccentricity, and whirling frequency on the cavitation in the film are investigated systematically and experimentally. The experimental results indicate that cavitation mainly affect the pressure in the negative pressure zone of the inner and outer film of DCSFD, but has little influence on the pressure in the positive pressure zone. The area of cavitation increased with eccentricity; when the inner eccentricity reached 0.1 or above, the area near the injection hole of film also generated a small zone of negative pressure. The numerical model and the experimental results in this paper are valuable for further research and engineering applications of DCSFD.